Evaluation of pore size distribution via fluid-fluid displacement porosimetry: The viscous bias. (April 2022) - Maalal, Otman; Prat, Marc; Peinador, René; Lasseux, Didier
Highlights: The fluid-fluid displacement porosimetry (FFDP) technique is analyzed. The FFDP technique is studied from pore network simulations Viscous effects introduce a bias in the identified pore size distribution (PSD) An optimization procedure is presented to correctly determine the PSD. Abstract: Fluid-fluid displacement porosimetry (FFDP) is a method for determining the pore size distribution of a porous medium from viscous fluid-fluid immiscible displacement (drainage) results, using a simplistic representation of the pore structure by cylindrical parallel tubes. The method leads to unambiguous estimates when the porous medium microstructure is strongly anisotropic and reasonably akin to this representation. The information obtained from this technique is however less straightforward to interpret for more complex microstructures. On the basis of synthetic data obtained from pore network simulations, it is evidenced, in particular, that this method leads to a shift in the distribution toward unrealistic small pore sizes. The shift, that may be very significant, is due to the viscous pressure drop in the displacing fluid. It is shown that significant improvement is achieved when the characterization of the pore size distribution is considered as an inverse optimization problem. The latter is solved using an optimization method presented in a previous work that was restricted to situations where viscous effects are unimportant.